Effects of sensorimotor training on functional and pain outcomes in achilles tendinopathy: a systematic review - Kim, Myoung-Hwee; Martin, Wille; Quarmby, Andrew; Stoll, Josefine; Engel, Tilman; Cassel, Michael (Frontiers in Sports and Active Living, 2024)
Considering the neuromuscular alterations in Achilles tendinopathy (AT), sensorimotor training (SMT) might be beneficial to restore the neuromuscular capacity of the muscle-tendon complex and thereby improve patients’ functions and alleviate symptoms. However, there is still a lack of knowledge concerning the effects of SMT on improving functional (e.g., strength) and pain outcomes in this population. Thus, the purpose of this study was to synthesize current evidence to analyze the efficacy of SMT in people with AT. A systematic electronic search was performed in PubMed, Web of Science, and Cochrane Central Register of Controlled Trials from inception to December 2023. Studies applying SMT in people with AT investigating functional or clinical pain outcomes were considered. Protocols had to incorporate balance, stabilization, proprioception, or vibration training. Patients with insertional or mid-portion AT (≥ 18 years age) diagnosed with clinical or sonographic evaluation were included. The search yielded 823 records. A total of three randomized controlled trials were considered eligible for the analysis. Each trial used a different SMT protocol: balance training, balance with stabilization training, or whole-body vibration training (WBVT) with other co-interventions. Most functional and pain parameters improved compared to baseline. The first study reported a decrease in pain and an increase in performance (i.e., countermovement jump height) and endurance (i.e., number of heel-raises) by 12-week use of a balance training in addition to isometric, concentric/eccentric, and eccentric exercises. The second study evaluated the four weeks effect of SMT (balance and stabilization training plus eccentric exercises) in addition to passive physiotherapy (deep frictions, ice, ultrasound), resulting in an increased plantarflexion peak torque and reduced pain levels. The third study investigating WBVT reported at 12 weeks an increase in flexibility and a decrease in tendon pain. SMT in addition to other co-interventions (i.e., eccentric, isometric, concentric/eccentric training, physiotherapy) showed improvements in strength, performance, flexibility, and alleviated pain outcomes. SMT might therefore be useful as part of a multimodal treatment strategy protocol in patients suffering from AT. However, due to the small number of studies included and the diversity of SMT protocols, the current evidence is weak; its additional effectiveness should be evaluated.